Secreted Behind Closed Doors : Rethinking Cather's Adultery Theme and "Unfurnished" Style in My Mortal Enemy - Adams, Janah R. (East Carolina University, 2011)
In recent years, My Mortal Enemy (1926) has been virtually ignored in Cather scholarship. I place the novel in its literary and critical context by building on information from the critical reception and recent scholarship on Cather's work to see how My Mortal Enemy fits into the expectations of Cather's writing at the time. A rejection of Cather's changing style at the time of the novels' reception and in more modern criticism has led to a rather narrow assessment of the novels' more ambiguous scenes and an overwhelming hostility toward its protagonist, obscuring the existence of other, more positive interpretations. I provide a close study of the novels' ambiguous scenes in relation to Cather's own discussion of her "unfurnished" style, and explore how critics may have misread these scenes and how we might utilize a new approach, one that takes into consideration Cather's interest and relation to the visual art scene of the time, to rethink assumptions about the novel and about its protagonist. I use Cather's 1923 novel A Lost Lady and the criticism that surrounded it to rethink My Mortal Enemy and provide a new way of reading the novel, solidifying My Mortal Enemy's place in the Cather canon and strengthening its value to the study of her life and works. By suggesting a fresh approach to the novel, I encourage readers of Cather's work to return to My Mortal Enemy to see what they too may have overlooked or misread in their first reading, in context of the novel itself, other novels by Cather, and the spirit of the time in which Cather lived and worked.
Keywords: American literature; Lost lady, A; Art; Modern; My mortal enemy; Cather, Willa, 1873-1947. My mortal enemy; Adultery in literature